2021
DOI: 10.3389/fpsyg.2020.549036
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Dual-Factor Model of Mental Health in the Mental Health Screening of Chinese College Students

Abstract: Traditional mental health models focus on psychopathological symptoms. In contrast, a dual-factor model of mental health integrates psychopathology and subjective well-being into a mental health continuum, and it is adjustment and supplement for traditional mental health research paradigm. The present study explores the applicability of a dual-factor model of mental health in mental health screening of Chinese college students. To assess mental health statuses of 2,065 college students, we used Flourishing Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
3
30
1
Order By: Relevance
“…Hence, the response patterns over the three dimensions of well-being among students with moderate mental wellbeing indicate possible different intervention needs. Differentiated functioning among students with moderate range mental health was reported in another recent study, showing college students reported different levels of life satisfaction and purposeful lifestyle across six mental health categorizations (Xiao et al, 2021). The six categorizations were based on respondents' positive mental health (high, moderate, and low) and the presence of depression symptoms.…”
Section: Five Mental Health Profilesmentioning
confidence: 80%
“…Hence, the response patterns over the three dimensions of well-being among students with moderate mental wellbeing indicate possible different intervention needs. Differentiated functioning among students with moderate range mental health was reported in another recent study, showing college students reported different levels of life satisfaction and purposeful lifestyle across six mental health categorizations (Xiao et al, 2021). The six categorizations were based on respondents' positive mental health (high, moderate, and low) and the presence of depression symptoms.…”
Section: Five Mental Health Profilesmentioning
confidence: 80%
“…Based on the research results of undergraduates and the general population, this study assumes that the DFM of mental health is better than the one-factor model. The mental health status of postgraduates will be classified with the DFM quartering method, and the results will be similar to those of the population (Renshaw and Cohen, 2014;Antaramian et al, 2015;Wang et al, 2016;Xiao et al, 2021). In addition, this study also focuses on the construction of positive factors of mental health and intends to find out the relationship between selfcompassion and help-seeking behavior and positive factors of mental health.…”
Section: This Studymentioning
confidence: 81%
“…Referring to the research of Xiao et al (2021), Flourishing Scale (FS) was used to measure the positive factors of mental health more robustly than life satisfaction (Diener et al, 2010). There are 8 items on the flourishing scale, which is scored on a 7-point Likert scale, with "1" representing strongly disagree and "7" representing strongly agree, all of which are scored positively, with a scoring range of 0-56.…”
Section: Measures Dual-factors Of Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The four subgroups differed significantly in locus of control, attention problems, alcohol abuse, hope, and gratitude [ 15 ]. The four subgroups also differed greatly in life satisfaction, sense of life, flourishing level, and depression [ 16 ]. The intervention plan for different mental health subgroups will be individualized, including reducing mental illness, and simultaneously working to improve well-being.…”
Section: Introductionmentioning
confidence: 99%